Tannic acid assisted metal–chelate interphase toward highly stable Zn metal anodes in rechargeable aqueous zinc-ion batteries - Hu, Nan; Qin, Hongyu; Chen, Xiangyou; Huang, Yanping; Xu, Jing; He, Huibing (Frontiers in Chemistry, 2022)
Aqueous zinc-ion batteries (AZIBs) have attracted extensive attention because of their eco-friendliness, intrinsic safety, and high theoretical capacity. Nevertheless, the long-standing Zn anode issues such as dendrite growth, hydrogen evolution, and passivation greatly restrict the further development of AZIBs. Herein, a metal–chelate interphase with high Zn affinity is constructed on the Zn metal surface (TA@Zn) via dipping metallic Zn into a tannic acid (TA) solution to address the aforementioned problems. Benefiting from the abundant hydrophilic and zincophilic phenolic hydroxyl groups of TA molecules, the metal–chelate interphase shows strong attraction for Zn2+ ions, guiding uniform zinc deposition as well as decreasing Zn2+ migration barrier. Therefore, the TA@Zn anode displays an extended lifespan of 850 h at 1 mA cm−2, 1 mAh cm−2 in the Zn|Zn symmetrical cell, and a high Coulombic efficiency of 96.8% in the Zn|Ti asymmetric cell. Furthermore, the Zn|V2O5 full cell using TA@Zn anode delivers an extremely high capacity retention of 95.9% after 750 cycles at 2 A g−1. This simple and effective strategy broadens the interfacial modification scope on Zn metal anodes for advanced rechargeable Zn metal batteries.